The Primary Glucose-Lowering Effect of Metformin Resides in the Gut, Not the Circulation: Results From Short-term Pharmacokinetic and 12-Week Dose-Ranging Studies - John B. Buse; Ralph A. DeFronzo; Julio Rosenstock; Terri Kim; Colleen Burns; Sharon Skare; Alain Baron; Mark Fineman (2015)
OBJECTIVE Delayed-release metformin (Met DR) is formulated to deliver the drug to the lower bowel to leverage the gut-based mechanisms of metformin action with lower plasma exposure. Met DR was assessed in two studies. Study 1 compared the bioavailability of single daily doses of Met DR to currently available immediate-release metformin (Met IR) and extended-release metformin (Met XR) in otherwise healthy volunteers. Study 2 assessed glycemic control in subjects with type 2 diabetes (T2DM) over 12 weeks. RESEARCH DESIGN AND METHODS Study 1 was a phase 1, randomized, four-period crossover study in 20 subjects. Study 2 was a 12-week, phase 2, multicenter, placebo-controlled, dose-ranging study in 240 subjects with T2DM randomized to receive Met DR 600, 800, or 1,000 mg administered once daily; blinded placebo; or unblinded Met XR 1,000 or 2,000 mg (reference). RESULTS The bioavailability of 1,000 mg Met DR b.i.d. was ∼50% that of Met IR and Met XR (study 1). In study 2, 600, 800, and 1,000 mg Met DR q.d. produced statistically significant, clinically relevant, and sustained reductions in fasting plasma glucose (FPG) levels over 12 weeks compared with placebo, with an ∼40% increase in potency compared with Met XR. The placebo-subtracted changes from baseline in HbA1c level at 12 weeks were consistent with changes in FPG levels. All treatments were generally well tolerated, and adverse events were consistent with Glucophage/Glucophage XR prescribing information. CONCLUSIONS Dissociation of the glycemic effect from plasma exposure with gut-restricted Met DR provides strong evidence for a predominantly lower bowel-mediated mechanism of metformin action.